Comparison of Commercial and Locally Identified Yeast Strains in Relation to Young Wine Quality of Cabernet Sauvignon - Sharma, A.K.; Sawant, S.D.; Adsule, P.G.; Rajguru, Y.R. (South African Journal of Enology and Viticulture, 2016)
The present study was conducted to evaluate the fermentation efficiency of locally identified yeast strains against the commercial yeast preparations in the case of Cabernet Sauvignon wines. For this purpose, must of Cabernet Sauvignon was inoculated separately with three each of commercial (KIV 1116, EC 1118 and Premier Cuvee) and locally identified (RS1, RS2 and RS3) yeast strains. The physicochemical parameters of wines made with these two groups of yeast strains showed significant differences during fermentation. The pH values ranged from 3.40 to 3.55, which fall in the agreeable limit. The minimum alcohol content, i.e. 10.32%, was found in the wine with maximum reducing sugars. Wine made from the inoculation of strain EC 1118 contained 11.06% alcohol. The anthocyanin content differed significantly among all the yeast strains. The maximum anthocyanin content was found in wine prepared from RS1 (15.70 g/l). Maximum colour intensity (14.66) was observed in the RS2 yeast strain. The wines made from locally identified yeast strains contained more antioxidant reducing power (FRAP) than commercially available yeast strains. Significant differences were noted among the yeast strains in relation to FRAP values. The locally identified yeast strains were found to be on par with commercial yeast strains. These strains can be used for further studies on other important varieties.